Checklist of the marine fishes of Turkey - Bilecenoglu, Murat; Taskavak, Ertan; Mater, Savas; Kaya, Murat (Zootaxa, 2002)
A checklist of the marine fish fauna of Turkey is presented for the first time. Examination of the previous studies revealed the presence of 448 species in 133 families. A total of 45 species, that has a doubtful presence at Turkish seas, was briefly discussed. The ichthyofaunal similarities of seas surrounding Turkey were compared, and the Black Sea and the Sea of Marmara were found to be 55.6% similar, whereas, the proportion computed for the Aegean and the Mediterranean Sea was 83.2%.